Development and Analysis on the PLC Based Sorting System for Recycle Purpose - Maruthapillai, Vasanthan; Vasanta Kumar, Dineish Kumar; Nordin, Nur Dalilah; Ibrahim, Izrulfizal Saufihamizal; Mohd Suhaimi, Shaffika; Chan, Bun Seng; Azmi, Aizat; Kasri, Nur Faizal; Mat Said, Dalila; Yunianta, Arda (Journal of Advanced Research Design, 2025)
In the world with frequent of trash-production and wastes that need to be disposed of, it usually takes a long time for these waste products to be recycled naturally. Some of the waste can affect the environment if it is not properly recycled, for example, plastic, metal, and glass. The purpose of this project is to develop an PLC based system in sorting different type of items to be recycled, such as glass, plastic, and metal can. This project involved programming of programmable logic controllers for a sorting process for objects to be recycled. The sensors were used to detect the material or object’s type, and this data was used as an input for the system to automatically separate them into three different categories based on the material. Pneumatic cylinder system was used as a pushing mechanism during sorting process. The probability of the constructed prototype in detecting type of material was analysed by testing it with seven objects: a plastic bottle, a plastic bag, a plastic case, a glass bottle, an aluminium can, a metal box, and a metal rod. The findings show that transparency, material type, and material strength significantly impact the results. A high probability in material detection primarily because of the hardness of the materials, facilitating easier differentiation. However, the detection of transparent materials posed challenges, and metal materials were consistently detected in nearly all tests. From the analysis, it is concluded that the current prototype system is still unable to provide high percentage of reliability to detect the materials of the selected object. Increasing the ability to detect the object type is necessary to ensure the success of developing this prototype for PLC based sorting system for recycle purpose. It is envisaged that this system can fasten the sorting process in the future. Besides, with automation application in such industry, there will be a reduced requirement for human labour for the repetitive tasks.